Cognitive deficits among supported employment clients with schizophrenia / Normala Sorikan - Normala, Sorikan (2019)
Cognitive deficits are related to impairment in functional abilities. As the goal of treatment for schizophrenia is broader in that it involves not only clinical remission but also functional recovery, employment is one aspect of the recovery process. In schizophrenia patients, they have more difficulties in maintaining rather than acquiring a job despite of on-going job support and coaching. The aim of this study is to examine the association of deficit in specific cognitive domains as the predictive factor of employment outcome.This is a cross-sectional study. Sixty two (n=62) participants who were enrolled under the supported employment programme in Hospital Permai for at least one month were recruited and categorized under either the working or terminated group (31 participants in each group). They were assessed with six cognitive tests that corresponded to three cognitive domains (processing speed, working memory and executive function) based on the MATRICS Consensus Cognitive Battery. The terminated groups were assessed for the reasons of termination using Job Termination Interview. The neurocognitive tests were done once and simultaneously between the two groups during the study period. There is a significant difference in the level of working memory, speed of processing and reasoning and problem solving between working and terminated group with p value < 0.001. Analysis on association between cognitive deficit and job termination showed there is significant association between deficit in working memory, speed of processing and executive function with job termination. However, from the multivariate analysis, among the three cognitive domains, only working memory deficit (p<0.05) has significant association with job termination.There is significant association between primary reason of termination and working memory deficit with p value < 0.05. The highest percentage of primary reason is problem with work quality among working memory deficit group. However, we are unable to prove that the work quality has significant association with working memory iv deficit by using logistic regression test. Deficit in working memory is significantly a predictor of employment outcome in schizophrenia patients despite of ongoing job support in supported employment program. Further studies with larger sample size are needed to explore this area of research. Pilot study on cognitive remediation therapy is also recommended.